Sistem Pendidikan Indonesia - Yola Septia Utami; Deli Meylindo; Asiyah Asiyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the development, challenges, and prospects of the Indonesian education system from a historical, regulatory, and curriculum perspective. Using a descriptive qualitative method with a library study approach, this study examines relevant literature, laws and regulations, and previous research findings. The study results indicate that the Indonesian education system is a dynamic entity, influenced by internal and external factors from the Hindu-Buddhist era, the arrival of Islam, colonialism, to the Reformation era and the Independent Curriculum. A strong legal basis through the 1945 Constitution and Law Number 20 of 2003 provides a basic framework for national education, but in practice, challenges still arise in the form of disparities in quality between regions, limited facilities, and educator readiness. The Independent Curriculum is one of the latest innovations that emphasizes flexibility, 21st-century competencies, and the Pancasila student profile, although its implementation faces technical and resource constraints. This research emphasizes the importance of consistent education policies, strengthening teacher competencies, and equalizing access and facilities as strategic steps in realizing the national goal of enlightening the nation's life and preparing a generation with character, innovation, and the ability to compete globally.